Impact of Beta-Blockers on Nonhead Injured Trauma Patients. Issue 7 (July 2016) - Hendrick, Leah E.; Schroeppel, Thomas J.; Sharpe, John P.; Alsbrook, Diana; Magnotti, Louis J.; Weinberg, Jordan A.; Johnson, Benjamin P.; Lewis, Richard H.; Clement, L. Paige; Croce, Martin A.; Fabian, Timothy C.
Catecholamine surge after traumatic injury may lead to dysautonomia with increased morbidity. Small retrospective studies have shown potential benefit of beta-blockers (BB) in trauma patients with and without traumatic brain injury (TBI). This study evaluates a large multiply injured cohort without TBI that received BB. Patients were identified from the trauma registry from January 1, 2003 to December 31, 2011. Patients who received >1 dose of BB were compared to controls. Patients with TBI, length of stay (LOS) < 2 days, and prehospital BB were excluded. Outcomes were mortality, intensive care unit (ICU) LOS, and LOS. Stepwise multivariable regression was used to identify variables significantly associated with mortality. During the study period, 19, 151 eligible patients were admitted. The mean age was 39 years. Most were male (74%) and most sustained blunt mechanism (75%). A total of 1854 (11%) patients received BB. BB patients had longer LOS (16 vs 6 days), ICU LOS (7 vs 1 days), and higher mortality (2.8 vs 0.5%) (all P < 0.001). Multivariable regression demonstrated no benefit to BB after adjusting for potential confounding characteristics [odds ratio (OR) 0.952; confidence interval (CI) 0.620–1.461]. In conclusion, in this largest study to date, patients receiving BB were older, more severely injured, and had a higher mortality. Unlike TBI patients, multivariable regression showed no benefit from BB in this population.